The use of shaping by relatives of autistic children to increase food intake. Issue 2 (3rd July 2019) - Martone, Maria Carolina Correa; Martone, Ricardo Correa; Arantes, Ana Karina Leme
ABSTRACT: This study made use of differential reinforcement and shaping to increase the variety of food items accepted by two boys with autism. In the first phase, three new food items were introduced to the participants and the acceptance response to the food was systematically increased. Food items were introduced in a multiple baseline design. In the second phase, the children started to eat more than one type of food item per meal by means of a changing criterion design. The procedure was implemented by the parents and carried out in the home environment of each child. At the end of the experiment, three other food items were defined for each child and parents were asked to follow the procedure learned without author's supervision. The results showed that the two participants started accepting food, expanded the number of food items consumed and that parents learned to introduce new foods into their children's diets.